Mutações genéticas da deficiência auditiva: avaliação comportamental e eletrofisiológica da audição sem e com prótese auditiva em crianças - Vieira, Eliara Pinto [UNIFESP] (2011)
The BMPs, the inductive proteins of bone growth since the beginning of their use have been evaluated in different experimental models aiming to determine their efficacy. We know that some substances can interfere positively or negatively when used in a systemic way or places associated with the BMP. Objective: this study objective to evaluate the possible interferences of antibiotic-therapy by using the active principle of cefazolin in an experimental model with rabbits. Methods: Two groups of female New Zealand rabbits underwent a lumbar spine inter-transverse artrodesys of segment L5-L6 using posterior approach. An homolog bone graft associated with a bio-compound (bovine BMP, 1,0mg and hydroxiapatita, 9,0mg) was used in the first group. The same procedure and bio-compound were used in the second group. However the animals were submitted to a prophylactic antibiotic-therapy with cefazolin starting two hours before the procedure and maintained for 24 hours after surgery. The animals were analyzed for 15 weeks, isolated in captivity and daily evaluated by a veterinarian under the clinical and neurological views and then euthanized, being the surgical pieces removed and submitted to a radiological and histological analysis. Results: For the first group the quantity and location of the implanted material varied among the individuals. However in most of the cases, the quantity and particles of homolog bone was insignificant and disperse along the soft tissue that covers the posterior region of the vertebrae. In the other cases, the particles with reabsorvation filled the reduced space between the transversal processes. For the second group, the quantity of material and its location also varied among the individuals. In most of the cases, several particles of homolog bone filled the space between the lateral processes whose bone neo-formation led to a trapping of these particles. All the cases showed formation in a higher or lower intensity of the cartilaginous tissue in the surface of the transverse processes. The radiological analysis showed in its relative frequency a higher frequency of complete fusion for group 2 when compared to group 1. Conclusion: Under the histological view for the model and experimental period analyzed, we inferred that, despite the fact that none of the proposed treatments had promoted a complete fusion of the vertebraes per bone tissue, the use of homolog bone + bovine BMPs associated with the use of cefazolin promoted a higher cartilaginous and bone formation with lower incidence of rejection of the material grafted in the doer area when compared to the group without the association of cefazolin. Under the radiological view, the relative analysis also showed to be superior in the group where cefazolin was used as a prophylactic antibiotic.